SIRIUS 4: a rapid tool for turning tandem mass spectra into metabolite structure information - Dührkop, Kai; Fleischauer, Markus; Ludwig, Marcus; Aksenov, Alexander A.; Melnik, Alexey V.; Meusel, Marvin; Dorrestein, Pieter C.; Rousu, Juho; Böcker, Sebastian (Nature methods, 2019)
Mass spectrometry is a predominant experimental technique in metabolomics and related fields, but metabolite structural elucidation remains highly challenging. We report SIRIUS 4 ( https://bio.informatik.uni-jena.de/sirius/ ), which provides a fast computational approach for molecular structure identification. SIRIUS 4 integrates CSI:FingerID for searching in molecular structure databases. Using SIRIUS 4, we achieved identification rates of more than 70% on challenging metabolomics datasets. SIRIUS 4 is a fast and highly accurate tool for molecular structure interpretation from mass-spectrometry-based metabolomics data.